Post-procedural quantitative flow ratio gradient and target lesion revascularization after drug-coated balloon or plain-old balloon angioplasty. (25th November 2020) - Kirigaya, H; Okada, K; Hibi, K; Akiyama, E; Kimura, Y; Matsuzawa, Y; Iwahashi, N; Maejima, N; Kosuge, M; Tamura, K; Kimura, K
Abstract: Background: Balloon angioplasty, including drug-coated balloon (DCB), is an important option of percutaneous coronary interventions (PCI), even in the drug-eluting stent era. Although quantitative coronary angiography (QCA) has been frequently used to determine the optimal endpoint of balloon angioplasty, physiological assessment may add incremental prognostic values. Quantitative flow ratio (QFR) has evolved as a novel 3D QCA-based physiological index to estimate fractional flow reserve without hyperemia nor pressure guidewire, offering both anatomical and functional lesion assessments. This study aimed to characterize post-procedural anatomical and physiological indexes by QFR and to compare their prognostic impacts on long-term clinical outcomes. Methods: This retrospective study included 98 patients with de novo (n=39) or in-stent restenosis (n=59) lesions who underwent PCI with DCB (n=69) or plain-old balloon angioplasty (POBA, n=29). All lesions were analyzed by QCA and QFR. QCA analysis measured lesion length, reference lumen diameter (RLD), minimum lumen diameter (MLD) and percent diameter stenosis (%DS) at pre- and post-procedures as anatomical indexes. QFR analysis measured post-procedural QFR of target vessel (QFR-vessel) and QFR-gradient (ΔQFR between proximal and distal segments of the lesion) as physiological indexes. Primary endpoint was target lesion revascularization (TLR) within 1-year post-procedure. Results: Target lesion profiles were as follows: lesion length 26.3±16.6 mm, RLD 2.90±0.70 mm, MLD 0.94±0.32 mm and %DS 79.3±18.6%. At post-procedure, MLD, residual %DS, QFR-vessel and QFR-gradient of target lesions were 1.88±0.49 mm, 34.7±10.6%, 0.84±0.13 and 0.06±0.04, respectively. During 1 year post-procedure, TLR occurred in 19 (19%) patients. Patients with TLR showed smaller MLD (1.66±0.45 mm vs. 1.93±0.49 mm, p=0.028) and QFR-vessel (0.79±0.03 vs. 0.85±0.01, p=0.06), and greater residual %DS (42.7±11.3% vs. 32.8±9.5%, p=0.0002) and QFR-gradient (0.12±0.06 vs. 0.04±0.02, p<0.0001) at post-procedure compared with those without. In multivariate analysis including several clinical characteristics and anatomical indexes, QFR-gradient at post-procedure was independently associated with TLR within 1-year, demonstrating higher prognostic value compared with post-procedural MLD and residual %DS (Figure). The receiver-operating characteristics curve analysis identified the best cut-off value of QFR-gradient as 0.08 for predicting 1-year TLR after balloon angioplasty, irrespective of balloon type (DCB or POBA) (Figure 1). Conclusions: Post-procedural QFR-gradient within the lesion was an independent and stronger predictor of subsequent TLR, compared with anatomical indexes. Further studies are warranted to investigate whether QFR guidance to optimize PCI procedure could improve clinical outcomes in patients with balloon angioplasty. Funding Acknowledgement: Type of funding source: None